(3GdeTjNI GdHZOGOjIs - (3GdSdaj , CMeO Hf eMeO Hf Sdag GdCUHgGfj, UOQ GdOjf CHh WGgQ,J (B576 (3g` s ((3EHQGgje Hf YKeGf Hf YjSi GdMQGfi s)
(3ChdgG (B:s
(3GdMOjK GdeQhi Yf CfS Hf eGdc (B: (3EPG JRhL GdYHO abO GSJced fUa Ojfg adjJb Gddg ajeG Hbi s
(3fSNI cJHJ ef fSNI MeGO Hf gHI Gddg GdMQGfi GdJi SeYgG ef GdeUfa ai GdGScfOQjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B75s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B624 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B249 s
Keywords: (3GdJGQjNs